THE EFFECTIVENESS OF THE MODEL OF MEANINGFUL TEACHING INTEGRATING CHARACTER EDUCATION IN IMPROVING ATTITUDE AND MATHEMATIC PROBLEM SOLVING ABILITY - Salamia; Dardiri, Achmad; Retnawati, Heri (International Journal of Psychosocial Rehabilitation, 2020)
The implementation of the Model of Meaningful Teaching Integrating Character Education (MTICE Model) supports one of the educational programs in Indonesia, which requires the learning environment to be integrated with character education in all subject matters. The main objective of the MTICE Model is to enhance students’ active involvement in teaching-learning processes and simultaneously to improve their mathematics learning achievement. This research aims to investigate the effectiveness of the MTICE Model in improving students’ attitude and mathematical problem-solving ability. It is a quasi-experiment involving one control group and one experimental group. The control group was taught by using the conventional teaching model, while the experimental one was taught by using the MTICE Model. The research sample of madrasah tsanawiyah (MTs) was established using the convenience sampling technique. The data were collected using a mathematic problem-solving ability test and a student attitude questionnaire. The data were analyzed using the one-way ANOVA at the significance level, and the finding shows that the implementation of the MTICE Model is effective in improving students’ learning achievement in attitude and mathematical problem-solving ability. Therefore, it is suggested that the MTICE Model be used in mathematics teaching-learning processes.